Obesidade abdominal, dinapenia e obesidade abdominal dinapênica como fatores associados à quedas em idosos residentes no município de São Paulo - Estudo SABE - Máximo, Roberta de Oliveira (2017)
Objective: The aim of the present study was to investigate associations between abdominal obesity/dynapenia/dynapenic abdominal obesity and a single fall/recurrent falls as well as determine the effect size of such associations using two cutoff points for dynapenia. Methods: A cross-sectional study was conducted with 1.063 older adults pertaining to the third wave of the Saúde, Bem Estar e Envelhecimento (SABE – Health, Wellbeing and Ageing) study. Abdominal obesity was defined as a waist circumference of >102 cm for men and > 88 cm for women. The following were the cutoff points for dynapenia: grip strength < 30 kg for men and < 20 kg for women or < 26 kg for men and < 16 kg for women. Dynapenic abdominal obesity was defined by the combination of abdominal obesity and dynapenia. Regarding the outcome, the individuals were classified as non-fallers, single fallers or recurrent fallers. Socioeconomic, neuropsychiatric and environmental factors as well as living habits, polypharmacy, health status and functionality were the control variables in the multinomial regression models. Results: Adopting a cutoff point of 30/20, only one association was found: dynapenic abdominal obesity and a single fall (RRR = 2.37; 95% CI: 1.48-3.80). However, adopting a cutoff point of 26/16, dynapenic abdominal obesity (RRR = 1.93; 95% CI: 1.09-3.44), abdominal obesity (RRR = 1.65; 95% CI: 1.08-2.52) and dynapenia (RRR = 1.77; 95% CI: 1.01-3.13) were associated with a single fall, with a larger effect size of the association with dynapenic abdominal obesity than the other two conditions. Moreover, dynapenia defined using the 26/16 cutoff point was associated with recurrent falls (RRR = 2.39; 95% CI: 1.19-4.82). Conclusions: The cutoff point used to define dynapenia affects associations between abdominal obesity/dynapenia/dynapenic abdominal obesity and a single fall/recurring falls. A cutoff point of 26/16 is better for identifying such associations.